Numerical optimisation of laser assisted friction stir welding of structural steel. (18th August 2019) - Ahmad, Bilal; Galloway, Alexander; Toumpis, Athanasios
ABSTRACT: Significant progress has been made on the implementation of friction stir welding (FSW) in the industry for aluminium alloys. However, steel FSW and other high-temperature alloys is still the subject of considerable research, mainly because of the short life and high cost of the FSW tool. Different auxiliary energies have been considered as a means of optimising the FSW process and reducing the forces on the tool during the plunge and traverse stages, but numerical studies on steel are particularly limited. Building on the state-of-art, laser-assisted steel FSW has been numerically developed and analysed as a viable process amendment. Laser-assisted FSW increased the traverse speed up to 1500 mm min −1, significantly higher than conventional steel FSW. The application of laser assistance with a distance of 20 mm from the rotating tool reduced the reaction force on the tool probe tip up to 55% when compared to standard FSW.